La huella de carbono y su impacto potencial sobre las exportaciones argentinas - María Victoria Lottici (Centro de Economía Internacional (CEI), 2012)
– At present, carbon footprint labelling is at the heart of debates on the environmental impact of products, but there are other environmental criteria related to the sustainability of products that could also have an impact on developing countries' exports in the future. Furthermore, this issue has proved to be highly dynamic and subject to constant change over time; it is thus clear that its evolution needs to be closely monitored in view of the diverse consequences it might have on the Argentine export sector. The present study shows how relevant the European Union is for Argentina as a destination market for Argentine export products that could be potentially affected by carbon footprint standards or labelling. The actions taken in the United Kingdom and France, where special attention is paid to the carbon footprint of food products sold in large retail chains, and the European Commission's initiative on Environmental Footprint of Products are outstanding examples of initiatives aimed at measuring carbon footprint. It was also found that the basket of exports likely to be affected by carbon footprint measurement schemes accounts for around one-fourth of Argentine exports to each of the destinations included in this study: the United Kingdom, France, the European Union, the United States and Japan. In 2007-2010, average exports of these products to the European Union reached USD 2.82 billion, which totalled 29.1% of Argentine exports of the affected products to the world. In turn, the United States accounted for 11.1% of total exports of affected products, whereas the share of Japan only reached 2.1%. France and the United Kingdom accounted for only a small portion of this trade: 1.8% and 2.4% respectively. A more detailed analysis - at the level of heading - reveals that the main Argentine exports which in 2007-2010 were destined to the main markets implementing carbon footprint labelling schemes corresponded to bovine meat and its preparations, wines, crustaceans and fish, citrus fruit, apples and pears and other fruit, fruit juices and natural honey. According to 2003 data, an analysis of the degree of vulnerability of Argentine products destined to other markets shows that the most vulnerable productive sectors were honey, fruit juices, tea and apples and pears as well as bovine, swine and ovine meat and meat preparations, citrus fruit, fruit, vegetables and canned vegetables, and olive oil.
Keywords: 330; Umweltbelastung; Export; Argentinien